MAKNA INTENSITAS KOMUNIKASI MELALUI WHATSAPP DALAM MEMBANGUN KEDEKATAN EMOSIONAL MAHASISWA DI ERA DIGITAL - Shovmayanti, Noor Afy; Riyandini, Adela; Dani Kurniawan (JURNAL KOMUNITAS, 2026)
The development of digital technology has influenced the way students build and understand interpersonal relationships, particularly through the use of the instant messaging application WhatsApp. Although high WhatsApp communication intensity is often considered a sign of emotional closeness, it does not always indicate deep emotional involvement. Based on students' experiences and perspectives, this study aims to understand how the intensity of WhatsApp communication shapes students' emotional closeness. This study employs a qualitative method and uses a phenomenological approach as its methodology. Data were collected through in-depth interviews with active students who use WhatsApp as their primary communication tool in daily student life. Research shows that WhatsApp is an important tool for expressing emotions, maintaining interactions, and building relationships with people in situations of physical distance. Communication intensity is defined as the level of emotional involvement, attention, and presence reinforced through quick responses and the use of communication features. However, emotional closeness is highly dependent on the quality of interactions and the context of the relationship, not just the frequency of communication. The study found that WhatsApp communication can effectively build emotional closeness if accompanied by significant emotional engagement.